Functioning of book trailers in the development of literary tourism popularization in the context of hashtag analysis - Bilushchak, Тetiana; Kolos, Sofia (Turystyka i Rozwój Regionalny, 2020)
Based on the analysis of hashtags, it was found that the use of a multimedia format of book presentation as a book trailer on social networks is an effective means of promoting literary tourism. With the help of the “goal tree” method, an information model of the functioning of book trailers in the development of literary tourism popularization was created. The creation of a “goal tree” in the study provided an opportunity at the stage of information modelling to show the subordination and relationship of goals, which demonstrates the division of the overall goal into sub-goals, objectives and individual actions.